Cloud-First Content Modernization: Migrating Legacy ECM to Secure, Scalable Cloud Platforms - Jayaram, Yashovardhan (International Journal of Emerging Research in Engineering and Technology, 2023)
Enterprise Content Management (ECM) systems have long served as foundational platforms for managing organizational information assets. However, traditional on-premises ECM architectures struggle to meet modern demands for scalability, agility, security, and cost efficiency. The emergence of cloud computing has accelerated a paradigm shift toward cloud-first content modernization strategies. This paper presents a comprehensive study on migrating legacy ECM systems to secure and scalable cloud platforms. It examines architectural challenges, security and compliance requirements, data migration complexities, and operational transformation considerations. A structured cloud-first migration methodology is proposed, integrating content assessment, risk mitigation, security-by-design, and phased modernization. Experimental evaluation based on enterprise migration scenarios demonstrates significant improvements in system performance, availability, cost optimization, and compliance posture. The findings confirm that cloud-first ECM modernization enables enterprises to unlock advanced analytics, automation, and artificial intelligence capabilities while ensuring regulatory compliance and long-term sustainability. This study contributes a systematic framework and empirical insights for organizations pursuing large-scale ECM cloud migration initiatives